Balancing Academic and Parental Responsibilities: Exploring the Role of University Day-Care Programs for Student Parents - Iin Afriyanti Umar; Irkham Zamzuri; Muhammad Fayyaz Mumtaz (UIII Press, 2026)
This study is intended to explore how university day-care programs can assist and provide aid to student parents in balancing their studies and parental duties. The methodology of this study uses qualitative research methods, with in-depth interviews being employed to explore the experiences, challenges, benefits and attitudes of student parents involved in university day-care facilities. Upon the research, the findings revealed that student parents face complex challenges in managing academic and child care responsibilities, highlighting the importance of effective time management and support systems. Additionally, the quality of day-care services offered by the university significantly influences their ability to face these responsibilities successfully. Feedback from student parents emphasized the need for universities to ensure quality care, provide necessary resources, and implement supportive policies. Moreover, recommendations from these participants include prioritizing a safe environment, credible administration, excellent instructors, appropriate curriculum, sufficient space, sanitation, a variety of activities, and effective communication with parents. Enhancing university day-care programs based on these findings can create a more supportive and inclusive environment for student parents, facilitating their ability to balance academic and parental responsibilities.